Health care financing in Africa: what does NHA estimates do reveal about the distribution of financial burden? (2013)
This paper, utilized National Health Accounts framework to profile the health financing situation in Sub- Saharan Africa countries. While Africa accounted for less than 0.9 percent of global health spending, the region carried over 43% of global burden of communicable diseases. Thus financing of healthcare remained a core issue to most African countries. The highest burden of healthcare financing is shouldered by households, which accounted for between 72% and 99% of private sources. The public and external sources accounted for around 33% and 30% of total health expenditure, respectively. With high poverty incidence in the continent, households are easily exposed to catastrophic spending risk. Health financing reforms that emphasis pooling mechanism, especially social health insurance is therefore required. Deviance to the Alma Alta Declaration, which laid precedence on preventive healthcare, curative healthcare generally, dominated the allocation of healthcare resources. This has implication on the efficiency and effectiveness of healthcare delivery in African countries. Public facilities played a dominant role in the provision of healthcare, which is arguably supported by the need to achieve greater equity in healthcare delivery. However, with the growing wave of public-private partnership initiatives, it may be intuitively wise and efficient to increase private participation in healthcare provision.